Kenya’s ICT policy in practice: The effectiveness of tablets and e-readers in improving student outcomes - Piper, Benjamin; Jepkemei, Evelyn; Kwayumba, Dunston; Kibukho, Kennedy (FIRE: Forum for International Research in Education, 2015)
Kenya is investing in information and communication technology (ICT) to improve children's learning outcomes. However, the literature on ICT is pessimistic about the ability of ICT alone to improve outcomes, and few ICT programs have created the instructional change necessary to increase learning. The Primary Math and Reading (PRIMR) Initiative implemented a randomized controlled trial of three ICT interventions to enhance learning outcomes: tablets for instructional supervisors, tablets for teachers, and e-readers for students. All three showed significant impacts in English and Kiswahili above the results of the control group. The impacts of the three interventions were not statistically significantly different from each other. Based on the findings, we recommend that Kenyan policy makers embed ICT interventions in a larger instructional reform, using ICT to support particular instructional improvement challenges. We also suggest that policy makers incorporate empirically derived cost-effectiveness analysis into investment decisions, to ensure that ICT provides value for money.
shortDOI: 10/ggjkvv KerkoCite.ItemAlsoKnownAs: 10.18275/fire201502011025 10/ggjkvv 2339240:APPT498R 2339240:D5IHJW9H 2339240:E5GA8GCG 2339240:EK3GAM3J 2339240:G6TBKSGI 2339240:IYCXFMIU 2405685:5IT5XZNT 2405685:DAU3FLGU 2405685:H9RNSJQE 2405685:J45J4EMF 2405685:V6F62IW5 2405685:WVNEPIB3 2405685:Y4AUMNW2 2534378:73A9DFAH 2534378:8Y5PJAGB 2534378:P2EJKSKD
Keywords: African Languages; Control Groups; Cost Effectiveness; ERIC; Current Index to Journals in Education (CIJE); Educational Policy; Educational Practices; Elementary Secondary Education; English (Second Language); Experimental Groups; Foreign Countries; Handheld Devices; Intervention; Kenya; Literacy; Outcomes of Education; Program Effectiveness; Randomized Controlled Trials; Reading Achievement; Student Improvement; Technology Uses in Education; __:import:01; __:match:final; __:matched; __:study_id:2096974; ___working_potential_duplicate; __finaldtb

Learning through Assistive Devices: A Case of Students with Hearing Impairment - Farooq, Muhammad Shahid; Aasma; Iftikhar, Umaira (Bulletin of Education and Research, 2015)
Present era has introduced persons with disabilities with a range of assistive devices that have rapidly increased their educational, vocational, and frivolous activities. Current descriptive study attempted to explore the effects of assistive devices on the learning of hearing impaired students. A sample of 200 hearing impaired students was selected to identify the assistive devices that are more in use by hearing impaired students. All of the assistive devices commonly used for hearing impairment were included in the study to explore the effects of each on the learning of students with hearing impairment. The mean difference in the learning of students suggested that assistive technologies are overall assistance for the students with hearing impairment and there is no substitute to these devices that could assist them in such a quite differentiated manner. The role of high tech assistive devices as well as low tech devices has been highlighted prominently. The parents of hearing impaired students were also the part of study and found satisfied with the use of assistive devices for their children. It is divulged that there is a need to reduce the cost of assistive devices to be used by the students with hearing impairment.
Publisher: Institute of Education and Research KerkoCite.ItemAlsoKnownAs: 2339240:BMZ8MTPR 2405685:GTZBXLQU
Keywords: Assistive Technology; Costs; Elementary School Students; Foreign Countries; Grade 4; Hearing Impairments; Interpersonal Communication; Parent Attitudes; Program Effectiveness; Quality of Life; Student Needs; ___working_potential_duplicate; ⛔ No DOI found

Learning through Assistive Devices: A Case of Students with Hearing Impairment - Farooq, Muhammad Shahid; Aasma; Iftikhar, Umaira (Bulletin of Education and Research, 2015)
Present era has introduced persons with disabilities with a range of assistive devices that have rapidly increased their educational, vocational, and frivolous activities. Current descriptive study attempted to explore the effects of assistive devices on the learning of hearing impaired students. A sample of 200 hearing impaired students was selected to identify the assistive devices that are more in use by hearing impaired students. All of the assistive devices commonly used for hearing impairment were included in the study to explore the effects of each on the learning of students with hearing impairment. The mean difference in the learning of students suggested that assistive technologies are overall assistance for the students with hearing impairment and there is no substitute to these devices that could assist them in such a quite differentiated manner. The role of high tech assistive devices as well as low tech devices has been highlighted prominently. The parents of hearing impaired students were also the part of study and found satisfied with the use of assistive devices for their children. It is divulged that there is a need to reduce the cost of assistive devices to be used by the students with hearing impairment.
KerkoCite.ItemAlsoKnownAs: 2339240:Z7WED3QU 2405685:L6EEZ9LR
Keywords: Assistive Technology; Costs; Elementary School Students; Foreign Countries; Grade 4; Hearing Impairments; Interpersonal Communication; Parent Attitudes; Program Effectiveness; Quality of Life; Student Needs; ___working_potential_duplicate; ⛔ No DOI found

Opportunities for Equitable Access to Quality Basic Education (OPEQ): Final Report on the Impact of the OPEQ Intervention in the Democratic Republic of Congo - Aber, J. Lawrence; Starkey, Leighann; Tubbs, Carly; Torrente, Catalina; Johnston, Brian; Wolf, Sharon; Shivshanker, Anjuli; Annan, Jeannie (2015)
KerkoCite.ItemAlsoKnownAs: 2339240:ABHT5QJ4 2405685:38QVMKG5

One Laptop per Child at home: Short-term impacts from a randomized experiment in Peru - Beuermann, Diether W.; Cristia, Julian; Cueto, Santiago; Malamud, Ofer; Cruz-Aguayo, Yyannu (American Economic Journal. Applied Economics, 2015)
This paper presents results from a randomized controlled trial whereby approximately 1,000 OLPC XO laptops were provided for home use to children attending primary schools in Lima, Peru. The intervention increased access and use of home computers, with some substitution away from computer use outside the home. Children randomized to receive laptops scored about 0.8 standard deviations higher in a test of XO proficiency but showed lower academic effort as reported by teachers. There were no impacts on academic achievement or cognitive skills as measured by the Raven's Progressive Matrices test. Finally, there was little evidence for spillovers within schools. (JEL I21, I28, J13, O15)
Num Pages: 28 Place: Nashville, United States Publisher: American Economic Association Section: Articles KerkoCite.ItemAlsoKnownAs: 10.1257/APP.20130267 10.1257/app.20130267 10/gd853r 2339240:27SMHV3H 2339240:CPRGCBM2 2339240:TELXF9WP 2405685:9EXLABVP 2405685:9FMQU6XN 2405685:XXVAITEK
Keywords: ACCESS TO LAPTOPS; Academic achievement; Achievement tests; Business And Economics; EXCLUSION CRITERIA APPLIED; Elementary school students; Portable computers; Quality: H; Relevance: M; Statistical analysis; ___working_potential_duplicate; publishPDF

Teacher coaching in Kenya: Examining instructional support in public and nonformal schools - Piper, Benjamin; Zuilkowski, Stephanie Simmons (Teaching and Teacher Education, 2015)
Instructional coaching has improved student outcomes in the United States, and may help to solve Kenya's literacy problems. Coaching is costly, however, and evidence is lacking regarding the most cost-efficient teacher-to-coach ratio. We used student literacy outcome data from more than 8000 students participating in the Kenya Primary Math and Reading Initiative—a randomized controlled trial of instructional interventions in public and nonformal schools—to fill this gap. Coaches in larger public zones made fewer visits per teacher, and teacher-coach ratio and student performance were negatively associated. Using causal methods, we concluded that lower ratios might improve nonformal school outcomes.
shortDOI: 10/f63z7b KerkoCite.ItemAlsoKnownAs: 10.1016/j.tate.2015.01.001 10/f63z7b 2339240:76EQG2NV 2405685:LM7EYD5E 2405685:WU59KPEH 261495:QBFNURGR
Keywords: AWP2; C:Kenya; CitedIn:AKFC; CitedIn:OER4Schools-HHH3-B; Coaching; Instruction; Kenya; Literacy; PRIMR; professional development

Autism screening and diagnosis in low resource settings: Challenges and opportunities to enhance research and services worldwide - Durkin, Maureen S.; Elsabbagh, Mayada; Barbaro, Josephine; Gladstone, Melissa; Happe, Francesca; Hoekstra, Rosa A.; Lee, Li-Ching; Rattazzi, Alexia; Stapel-Wax, Jennifer; Stone, Wendy L.; Tager-Flusberg, Helen; Thurm, Audrey; et al. (Autism Research: Official Journal of the International Society for Autism Research, 2015)
Most research into the epidemiology, etiology, clinical manifestations, diagnosis and treatment of autism is based on studies in high income countries. Moreover, within high income countries, individuals of high socioeconomic status are disproportionately represented among participants in autism research. Corresponding disparities in access to autism screening, diagnosis, and treatment exist globally. One of the barriers perpetuating this imbalance is the high cost of proprietary tools for diagnosing autism and for delivering evidence-based therapies. Another barrier is the high cost of training of professionals and para-professionals to use the tools. Open-source and open access models provide a way to facilitate global collaboration and training. Using these models and technologies, the autism scientific community and clinicians worldwide should be able to work more effectively and efficiently than they have to date to address the global imbalance in autism knowledge and at the same time advance our understanding of autism and our ability to deliver cost-effective services to everyone in need.
KerkoCite.ItemAlsoKnownAs: 10.1002/aur.1575 2339240:VPT8E92I 2405685:ZJU7T2BU
Keywords: Autistic Disorder; Developing Countries; Global Health; Health Services Accessibility; Humans; Internationality; Research; diagnosis; early detection; epidemiology; intervention

Teaching and Learning Materials Financing - Read, Tony (Where Have All the Textbooks Gone?: Toward Sustainable Provision of Teaching and Learning Materials in Sub-Saharan Africa, 2015)
Suggests that no single universal cause behind the persistent under-financing of textbook provision in Sub-Saharan Africa (SSA) countries exists, but some common components include, (1) the pressure on teaching and learning materials (TLM) budgets caused by rapid enrollment growth; (2) the repeated tendency for curriculum designers to make decisions without taking into account the cost implications on the system as a whole; (3) the failure of development partner (DP) support to addressed affordability and sustainability issues; (4) the misunderstanding of ministries of education (MOEs) and DPs concerning manufacturing versus textbook cost as well as textbook versus system cost; (5) the lack of review and management of the nature and extent of fund diversion, fund misappropriation, piracy, and price mark-ups in undermining allocated TLM funding; and (6) the lack of monitoring, inspection, supervision, and financial audit systems necessary to ensure that all links in the financing and supply chain operate effectively.
KerkoCite.ItemAlsoKnownAs: 10.1596/978-1-4648-0572-1_ch5 2339240:KH9KW2WE 2405685:ZZ9HPXR7

Designing a program of teacher professional development to support beginning reading acquisition in coastal Kenya - Dubeck, Margaret M.; Jukes, Matthew C.H.; Brooker, Simon J.; Drake, Tom L.; Inyega, Hellen N. (International Journal of Educational Development, 2015)
What should be considered when developing a literacy intervention that asks teachers to implement new instructional methods? How can this be achieved with minimal support within existing policy? We argue that two broad sets of considerations must be made in designing such an intervention. First, the intervention must be effective by bridging the gap between current teacher practice and the scientiﬁc literature on effective instruction. This broad consideration is detailed with 10 design recommendations. Second, the intervention must be amenable to being scaled-up and mainstreamed as part of government policy. This involves being (i) simple and replicable; (ii) well received by teachers; and (iii) cost effective. The paper describes how these factors were considered in the design of a literacy intervention in government primary schools in coastal Kenya. It also includes reactions from teachers about the intervention and their change in knowledge.
shortDOI: 10/f7fghr KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2014.11.022 10/f7fghr 2405685:4WTUAF8V 2405685:USCCYKCK 2534378:5GJ88R44 2534378:DLHXICEY 2534378:NIUAY2PP
Keywords: ADULTS; BEST practices; EDUCATION; EDUCATIONAL innovations; EDUCATIONAL intervention; ELEMENTARY education; KENYA; Kenya; LITERACY; Literacy; Perception; Reading instruction; TEACHER development; TEACHING methods; Teacher education; Text messages; __:import:01; __:match:final; __:matched; __:study_id:2099920; ___working_potential_duplicate; __finaldtb

Does computer-assisted learning improve learning outcomes? Evidence from a randomized experiment in migrant schools in Beijing - Lai, Fang; Luo, Renfu; Zhang, Linxiu; Huang, Xinzhe; Rozelle, Scott (Economics of Education Review, 2015)
The education of the disadvantaged population has been a long-standing challenge to education systems in both developed and developing countries. Although computer-assisted learning (CAL) has been considered one alternative to improve learning outcomes in a cost-effective way, the empirical evidence of its impacts on improving learning outcomes is mixed. This paper uses a randomized field experiment to explore the effects of CAL on student academic and non-academic outcomes for students in migrant schools in Beijing. Our results show that a remedial CAL program held out of regular school hours improved the student standardized math scores by 0.15 standard deviations and most of the program effect took place within 2 months after the start of the program. Students with less-educated parents benefited more from the program. Moreover, CAL also significantly increased the students’ interest in learning.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.econedurev.2015.03.005 2339240:4J6WADM5 2405685:3LTP3SLM
Keywords: China; Computer-assisted learning; Development; Education; Migration; Random assignment; Test scores

Designing a program of teacher professional development to support beginning reading acquisition in coastal Kenya - Dubeck, Margaret M.; Jukes, Matthew C.H.; Brooker, Simon J.; Drake, Tom L.; Inyega, Hellen N. (International Journal of Educational Development, 2015)
What should be considered when developing a literacy intervention that asks teachers to implement new instructional methods? How can this be achieved with minimal support within existing policy? We argue that two broad sets of considerations must be made in designing such an intervention. First, the intervention must be effective by bridging the gap between current teacher practice and the scientific literature on effective instruction. This broad consideration is detailed with 10 design recommendations. Second, the intervention must be amenable to being scaled-up and mainstreamed as part of government policy. This involves being (i) simple and replicable; (ii) well received by teachers; and (iii) cost effective. The paper describes how these factors were considered in the design of a literacy intervention in government primary schools in coastal Kenya. It also includes reactions from teachers about the intervention and their change in knowledge. [ABSTRACT FROM AUTHOR]
Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.ebscohost.com/login.aspx?direct=true&db=bri&AN=108296506&site=ehost-live&scope=site KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2014.11.022 2339240:B8GCJR9U 2405685:7W777384 2534378:5GJ88R44 2534378:DLHXICEY 2534378:NIUAY2PP
Keywords: ADULTS; BEST practices; EDUCATION; EDUCATIONAL innovations; EDUCATIONAL intervention; ELEMENTARY education; KENYA; Kenya; LITERACY; Literacy; Perception; Reading instruction; TEACHER development; TEACHING methods; Teacher education; Text messages; __:import:01; __:match:final; __:matched; __:study_id:2099920; __finaldtb

Conducting Semi-Structured Interviews - Adams, William C. (Handbook of Practical Program Evaluation, 2015)
Conducted conversationally with one respondent at a time, the semi-structured interview (SSI) employs a blend of closed- and open-ended questions, often accompanied by follow-up why or how questions. About one hour is considered a reasonable maximum length for SSIs in order to minimize fatigue for both interviewer and respondent. This chapter begins with a discussion on the disadvantages and advantages of SSIs. Despite the disadvantages and costs of SSIs, they offer some extraordinary benefits as well. Semi-structured interviews are superbly suited for a number of valuable tasks, particularly when more than a few of the open-ended questions require follow-up queries. The chapter presents some recommendations that can be considered when constructing an SSI guide. All in all, effectively conducted semi-structured interviews, even though labor intensive, should be worth the effort in terms of the insights and information gained.
Section: 19 _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/9781119171386.ch19 KerkoCite.ItemAlsoKnownAs: 10.1002/9781119171386.ch19 2339240:69ZTFIC2 2405685:VQD9I55K
Keywords: SSI guide; open-ended questions; semi-structured interviews

The Use of Information and Communication Technology (ICT) for Knowledge Management in the Second Cycle Educational Institutions in Ghana - Ohemeng, Patrick; Twum, Edward; Nii, Isadore (International Journal of Computer Applications, 2015)
Given its capabilities to widen access, improve the quality and reduce the cost of developing, accessing and maintaining information, Information and Communication Technology (ICT) offers increased possibilities for managing knowledge. This paper thus investigates the level of utilization of ICT in the knowledge management processes in the Ghanaian educational system. Being a descriptive study, a randomly selected sample of second cycle educational institutions was surveyed through questionnaire. Using descriptive data analysis, the study found a low level of Information and Communication Technologies usage in knowledge management processes in the second cycle educational system. Knowledge management practices were found to be inefficient due to, among other things, absence of strategic policies and nonutilization of ICT. The findings indicate that the Secondary Schools are not deriving the efficiency returns of the computers they have acquired due to the absence of a deliberate and effective strategy for knowledge management. Also students, teachers and administrators in the second cycle schools are not benefitting from the information revolution for knowledge management. It was recommended that capacity building in knowledge management and improvement of Internet speed should be given priority attention by educational authorities.
KerkoCite.ItemAlsoKnownAs: 10.5120/ijca2015906600 2339240:MY59MT5E 2405685:R9EMPF5Y